Urban Form and Transportation Energy Consumption in Depok, Indonesia - Devina Widya Putri; Petrus Natalivan Indradjati (Faculty of Geography, Universitas Gadjah Mada, 2022)
By combining transportation energy use per capita for main, side, and weekend activities, this study explores the correlation between transportation energy consumption and urban form at a village scale. Conducted in Depok, a satellite city of the Jabodetabek metropolitan area, Indonesia, four different urban form variables were measured, including population density, land use mix, street connectivity, and public transportation range area. Four other socio-economic variables, i.e., private vehicle ownership, driving license ownership, job type, and monthly income, were also considered in the analysis. Data on individual energy consumption in the transportation sector was acquired through an online questionnaire. The results of correlation analysis and one-way analysis of variance highlighted three main findings related to transportation energy consumption. First, the population density and the street connectivity were found to be correlated with the amount of transportation energy consumed. Second, the middle urban form compactness level outweighed the high compactness level in terms of energy consumption per capita per week. Finally, differences in private vehicle ownership, driving license ownership, and job type resulted in different transportation energy usage.